A new attack on special-structured RSA primes - Abd Ghafar, Amir Hamzah; Kamel Ariffin, Muhammad Rezal; Asbullah, Muhammad Asyraf (Institute for Mathematical Research, Universiti Putra Malaysia, 2019)
RSA cryptosystem has withstand a number of cryptanalysis over the years on its mathematical structures. The cryptanalysis provides the users of the cryptosystem some particular cases where the RSA private keys can be exposed hence diminishes its security elements. In this paper, we discusses a general case of our previous attack on RSA primes. Our attack corresponds to the special-structured RSA primes namely the primes are relatively close to their nearest squared numbers. We also count the number of primes that are vulnerable to our attack. Finally, we present the countermeasure that can be implemented in the RSA key generation algorithm to avoid our attack.